Abordagem metodológica de investigação das redes inter-firmas sob a perspectiva de estratégia de operações - Gobbo Junior, José Alcides; Vasconcellos, Marcos Augusto de; Salgado, Manoel Henrique; Castro, Rosani de (Revista Gestão da Produção Operações e Sistemas, 2006)
Most studies available about operations strategy have been done under the business unit paradigm (SKINNER,1969; HAYES e WHEELWRIGHT, 1984; FINE e HAX, 1985; SAMSON, 1991; HILL, 2000). Recently, it hasbeen proposed other extended and up-to-date approach for the operations strategy field, but still working underthe business units paradigm (SLACK e LEWIS, 2002) and business units and intra-firm networks paradigm(RUDBERG e OLHAGER, 2003; HAYES et al., 2004). However, nowadays the new paradigm of inter-firmnetworks competition determines the need for studies under a more holistic approach. This paper presents theresults of a field research to verify the validity of the manufacturing strategy theory, which has been developedunder a business unit paradigm, under an inter-firm networks perspective. For that, it was necessary to makesome adaptations on the existing methodological approaches and theoretical ground for operations strategy, tocope with the specificities presented by inter-firm networks. Under this context, this article presents onemethodological approach to extend the scope of two decision areas of operations strategy (vertical integrationand facilities) but considering an inter-firm networks perspective. Additionally, the paper presents an exampleinvolving a qualitative and exploratory research to illustrate the utility of the proposed approach in an interfirmnetwork. Preliminary results obtained by the survey suggest the validity of the extended model.Key-words: Inter-firm networks; Operations strategy; Network project.